The Total Alkaloid Content, Tyrosinase Inhibitory Activity, and Anti-Acne Properties of Toona sureni (Blume) Merr. Leaves Extracts at Varying Tree Ages - Falah, Syamsul; Safithri, Mega; Zuraida, Zuraida; Lastini, Tien; Ariyanti, Riska; Marwanto, Yoga Dwi; Rahmania, Fitriani Jati (Indonesian Journal of Chemistry, 2026)
Toona sureni (Blume) Merr., known as Indonesian mahogany, is valued for its wood, while its leaves are used as vegetables and animal feed. However, its medicinal potential remains underexplored. This study evaluated the antibacterial and tyrosinase inhibitory activities of T. sureni leaf extracts from 16-, 27-, and 34-year-old trees. Extraction was performed by maceration using methanol, ethyl acetate, and n-hexane for antibacterial testing; and 30, 70, and 96% ethanol for tyrosinase inhibition. Total alkaloid content was determined using the bromocresol green method, while antibacterial activity was assessed by disc diffusion and MIC, and tyrosinase inhibition by spectrophotometry using kojic acid as a control. It revealed a 3.83% alkaloid content in the 70% ethanolic leaves extract of the 34-year-old tree. The 96% ethanolic extract from 16-year-old leaves exhibited the highest tyrosinase inhibitory activity at 86.66% with an IC50 value of 53.71±1.04 μg/mL. Antibacterial tests revealed that the methanol extract of 16-year-old trees inhibited Staphylococcus aureus (17.73 mm) and Propionibacterium acnes (15.80 mm) at 10,000 μg/mL, with MIC of 1000 and 500 μg/mL, respectively. These results suggest that the extract of 16-year-old tree has both antibacterial and tyrosinase inhibitory effects, with greater potential for cosmetic use, particularly in anti-acne and skin-brightening products.